PENGEMBANGAN VARIASI LATIHAN SERVICE ATAS UNTUK PESERTA EKSTRAKURIKULER BOLAVOLI DI SMK NEGERI 4 MALANG - Pinton Setya Mustafa; M. E. Winarno; Asim Asim (Jurnal Pendidikan Jasmani)
Abstract: In the game of volleyball it is necessary to start the service techniques. Overhand service is one type of service with the technique of hitting the ball with one hand and impact the ball with your hands over the front of the head. Based on observations made on extracurricular volleyball at SMK Negeri 4 Malang, namely: the process of training service on only done with the drill in the service area. This research aims to develop a variety of training service on volleyball. Research and development using procedural models of Borg and Gall were modified to 7 steps. Product development services on a variety of exercises is valid and practical to use for participants extracurricular volleyball at SMK Negeri 4 Malang. Product development consists of nine product specifications.Keywords: variations in training, overhand service, extracurricular volleyball.Abstrak: Dalam memulai permainan bolavoli diperlukan teknik service. Service atas adalah salah satu jenis service dengan teknik memukul bola dengan satu tangan dan perkenaan bola dengan tangan berada di atas depan kepala. Berdasarkan observasi yang dilakukan pada ekstrakurikuler bolavoli di SMK Negeri 4 Malang, yaitu: proses latihan service atas hanya dilakukan dengan drill di area service. Penelitian ini bertujuan untuk mengembangkan variasi latihan service atas bolavoli. Penelitian dan pengembangan ini menggunakan model prosedural dari Borg and Gall yang dimodifikasi  menjadi 7 langkah. Produk pengembangan variasi latihan service atas ini valid dan praktis digunakan untuk peserta ekstrakurikuler bolavoli di SMK Negeri 4 Malang. Produk pengembangan ini terdiri dari 9 spesifikasi produk.Kata kunci: variasi latihan, service atas, ekstrakurikuler bolavoli.